Chylomicronemia Syndrome in Pregnancy: a Case Report of an Acute Necrotizing Pancreatitis - Bolla, D.; Schyrba, V.; Drack, G.; Schöning, A.; Stage, A.; Hornung, R. (Geburtshilfe und Frauenheilkunde, 2012)
Introduction: Chylomicronemia syndrome (CS) is a rare disorder characterized by a high level of triglycerides in plasma. We present a case of a pregnant woman with a severe acute pancreatitis (AP) affected by a CS. Case: A 38-year-old gravida 2, para 0 with an uneventful course of pregnancy was referred with an AP at 37 0/7 weeks of gestation. This diagnosis was made from a nearby hospital where the chemical analysis showed elevated pancreatic enzymes with significant hypertriglyceridemia. Because of a pathological fetal heart tracing a caesarean delivery was performed. The APGAR score of the female newborn was 5/8/8 at 1, 5 and 10 minutes, respectively. The pH from the umbilical cord were 7.26 (artery) and 7.59 (vein). Once transferred to our intensive care unit a computer tomography scan confirmed an onset of a necrotizing AP. A conservative treatment was tried without success. For this reason a surgical debridement of the infected and necrosic parts was performed. After a long hospitalisation the patient could be dismissed after 2.5 months in good general condition. Discussion: Lipid profile changes in normal pregnancy are characterized by an elevation of total plasma cholesterol and triglyceride levels. This is normally caused by an increased liver synthesis of triglycerides in response to elevated estrogen levels. When a CS is diagnosed the main goal is to maintain fasting triglyceride levels at less than 500 mg/dL to reduce the risk for AP. Conclusion: Practitioners have an important role in evaluating chylomicronemic patients and implementing therapeutic lifestyle and pharmaceutic interventions aimed to reduce the risk for AP.
Keywords: delivery; obstetrics; metabolic defects